2022
DOI: 10.20473/ijtid.v10i1.32209
|View full text |Cite
|
Sign up to set email alerts
|

The Longevity of Aedes aegypti Larvae in Several Water Sources in Surabaya

Abstract: Aedes aegypti transmits the dengue virus that causes Dengue Viring the high number of DVI cases is the existing breeding places of Ae. aegypti. The water sources used by the community and the surrounding environment are essential media for living Ae. aegypti larvae. This recent study aimed to detect the longevity of Ae. aegypti larvae in diff erent water sources in Surabaya and the killing effect of temephos. An analytical observational and experimental study was conducted in August-September 2021. Twenty-instar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…This difference was probably due to the different turbidity levels that inhibit calculating the larvae attached to the wall of the container. A study about the longevity of Aedes aegypti larvae in several water sources concluded that rainwater with abate (temephos) resulted in the highest number of pupae [33]. Rainwater is the most preferred medium for hatching eggs of Aedes aegypti, with an average of 3-4 heads/day [34].…”
Section: Resultsmentioning
confidence: 99%
“…This difference was probably due to the different turbidity levels that inhibit calculating the larvae attached to the wall of the container. A study about the longevity of Aedes aegypti larvae in several water sources concluded that rainwater with abate (temephos) resulted in the highest number of pupae [33]. Rainwater is the most preferred medium for hatching eggs of Aedes aegypti, with an average of 3-4 heads/day [34].…”
Section: Resultsmentioning
confidence: 99%